2010
DOI: 10.1093/hmg/ddq312
|View full text |Cite
|
Sign up to set email alerts
|

Centromere protein A dynamics in human pluripotent stem cell self-renewal, differentiation and DNA damage

Abstract: Human pluripotent stem cells (hPSCs) hold significant promise for use in regenerative medicine, or as a model to understand human embryo development. However, the basic mechanisms required for proliferation and self-renewal of hPSCs have not been fully uncovered. Proliferation in all eukaryotes is dependent upon highly regulated expression of the histone H3 variant Centromere protein A (CENP-A). In the current study, we demonstrate that hPSCs have a unique messenger ribonucleic acid (mRNA) reserve of CENP-A no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
30
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 56 publications
5
30
0
Order By: Relevance
“…Lentiviral vectors were packaged, concentrated by ultracentrifugation at 50 000 g for 90 min, resuspended in hESC media and stored at −80° C as previously described [12]. Tittering was performed on Human Embryonic Kidney 293 FT cells.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Lentiviral vectors were packaged, concentrated by ultracentrifugation at 50 000 g for 90 min, resuspended in hESC media and stored at −80° C as previously described [12]. Tittering was performed on Human Embryonic Kidney 293 FT cells.…”
Section: Methodsmentioning
confidence: 99%
“…Tittering was performed on Human Embryonic Kidney 293 FT cells. Transduction in hESCs line was performed at MOI 1 as previously described [12]. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, decreased levels of kinetochore proteins cause different responses in different cell types. For example, depletion of CENP-A protein in fibroblasts eliminates kinetochore function, while the same knockdown permits cell cycle progression in human pluripotent stem cells, presumably because they have stored CENP-A mRNA, further protecting them from CENP-A depletion [81]. …”
Section: Kinetochore Complex Numbermentioning
confidence: 99%
“…The senescence that arises from CENP-A depletion may be a self-defense mechanism to suppress the otherwise catastrophic impact upon genome integrity that would arise from kinetochore dysfunction following certain types of stress. It should be noted that reduction of CENP-A does not result in irreversible growth arrest in human pluripotent stem cells (Ambartsumyan et al, 2010). Ambartsumyan et al demonstrated that CENP-A-depleted undifferentiated human pluripotent stem cells were capable of maintaining a functional centromere marks and showed no changes in morphology or proliferation rate relative to control cells, whereas CENP-A-depleted BJ fibroblasts showed arrest in G2/M and underwent apoptosis.…”
Section: Cenp-a Has An Impact On Cell Proliferationmentioning
confidence: 99%